Charged-hadron suppression in Pb plus Pb and Xe plus Xe collisions measured with the ATLAS detector - Onofre, A. (2019)
The ATLAS detector at the LHC recorded 0.49 nb−1 of Pb+Pb collisions and 25 pb−1 of pp collisions, both at the center-of-mass energy 5.02 TeV per nucleon pair. Recently, ATLAS also recorded 3μb−1 of Xe+Xe collisions at the center-of-mass energy 5.44 TeV, which provides a new opportunity to study the system-size dependence of the charged-hadron production in heavy-ion collisions. The large acceptance of the ATLAS detector allows to measure the spectra of charged hadrons in a wide range of pseudorapidity and transverse momentum. The nuclear modification factors RAA are constructed as a ratio of the spectra measured in Pb+Pb or Xe+Xe collisions to that measured in pp collisions. The RAA obtained in the two systems are presented for different centrality intervals and the results are discussed.